THE INFLUENCE OF TYPICAL WEST JAVA SOUVENIRS ON THE LEVEL OF DOMESTIC TOURIST VISITS IN THE CITY OF BANDUNG, WEST JAVA - Mila karmila,; Tuti Iriani,; R. Soni Sumali,; E. Yuyun Kustini,; Risma Julistiana,; Arman Syah Putra, (Journal of Innovation Research and Knowledge, 2022)
The background of this research is to find out what variables can affect a city, and the city chosen in this study is the city of Bandung, the variables raised in this study are typical food of the city of Bandung which can be used as souvenirs domestic tourist visits in the city of Bandung. The method used in this study is to use quantitative methods and use survey media as a tool in this study. This research conducted a survey of 100 residents of Bandung city who did tourism in the city of Bandung. The problem raised in this research is how to find out the variables that can affect a developing city in order to make the city more advanced than the occupancy rate of tourists who visit both domestically and internationally. The purpose of this research is how to find out the results of a variable affecting other variables. The variables that influence in this research are the typical food variable that can be used as souvenirs and the variable of domestic tourist visits to the city of Bandung.